An Improved Decision Making Grid Model to Identify Maintenance Strategies - M.A., Burhanuddin; A.R., Ahmad; M.I., Desa; Anton, S P (Universiti Teknologi Petronas and and Institution of Mechanical Engineers, 2008)
Manufacturing industries in developing economies must produce marketable products and always meet the standards expected by their customers. This requires the investment in technology management in supporting daily operation and maintenance. Whenever there is a huge number of machines in production lines, then there will be a heavy duty of the maintenance activities. This paper shows on how to carry out computations for calculating frequency of failures and downtimes using Decision Making Grid (DMG). Then extend the theoretical and formulation in DMG using tri-quadrant approach to cluster and categorize the variables. Real dataset on machines maintenance in manufacturing industry is used to test and show the results.